Effects of mechanical vibration applied in the opposite direction of muscle shortening on maximal isometric strength - Silva, H. R.; Couto, B. P.; Szmuchrowski, L. A. (The Journal of Strength and Conditioning Research, 2008)
Most studies about human responses to mechanical vibrations involve whole-body vibration and vibration applied perpendicularly to the tendon or muscle. The aim of the present study was to verify the effects of mechanical vibration applied in the opposite direction of muscle shortening on maximal isometric strength of the flexor muscles of the elbow due to neural factors. Conventional isometric training with maximal isometric contractions (MVCs) and isometric training with vibrations were compared. Nineteen untrained males, ages 24 ± 3.28 years, were divided into 2 training groups. Group 1 performed conventional isometric training and group 2 isometric training with mechanical vibrations (frequency of 8 Hz and amplitude of 6 mm). Both groups executed 12 MVCs with a duration of 6 seconds and 2-minute intervals between the repetitions. The subjects trained 3 times per week for 4 weeks. The strength of the group subjected to vibrations increased significantly by 26 ± 11% (p < 0.05), whereas the strength of the group with conventional isometric training increased only 10 ± 5% (p < 0.05). These data suggest that training with vibrations applied in the opposite direction of muscle shortening enhances the mechanism of involuntary control of muscle activity and may improve strength in untrained males. Since these findings were in untrained males, further studies with athletes are necessary in order to generalize the results to athletes' training, although it seems that it would be possible.